ANALYSIS OF FARMING BUSINESS AND STRATEGY FOR INCREASING CORN PRODUCTION (ZEA MAYS) - Susan Novrini; Murni Sari Rahayu; Surya Dharma; Mhd. Ilham Riyadh; Henny Pratiwi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
The research objectives were: (1) to find out how much corn farming income was in the research area, (2) to find out the efficiency level of farming income in the research area, (3) to find out strategies for increasing production in the research area. The sampling method uses saturated sampling method (census) with a sample of 30 farmers, the data used are primary and secondary data. Data were analyzed using I = TR-TC to calculate income, to calculate the level of efficiency a = R/C, and SWOT analysis. The results showed that the average income of corn farmers per hectare in Sena Village was Rp. 6,455,000. R/C value of 1.51 means corn farming is efficient and feasible to cultivate. From the results of the IE matrix, it can be found that the internal X point is 0.9 and the Y point is 0.